On the differences between the two widely distributed and closely related rock shrimps Sicyonia japonica Balss, 1914 and S. parajaponica Crosnier, 2003 (Dendrobranchiata, Penaeoidea, Sicyoniidae), with a new record of S. japonica from Taiwan - Yang, Chien-Hui; Kumar, Appukuttannair Biju; Chan, Tin-Yam (Zootaxa, 2024)
The rock shrimp Sicyonia japonica Balss, 1914 is recorded from Taiwan for the first time. The availability of many fresh specimens of S. japonica and S. parajaponica Crosnier, 2003 from various localities in the Indo-West Pacific allowed a detailed comparison of the morphology, fresh coloration and genetics between these two closely related species. Their major differences are illustrated by line drawings, micro-computed tomography (micro-CT) images and color photographs. DNA barcoding comparison supports the specific status of these two species and reveals that the western Indian Ocean material of S. japonica may represent another cryptic taxon.